Changes of patience undergoing hemodialysis - Abad, Aidane C.; Cura, Paul John B .; Ison, Lazaro Ian A.; Lopez, Nadine L.; Moyano, Cristina P.; Reyes, Glenn Russel P. (Paranaque City: Olivarez College, 2015)
This study aims to elucidate the changes of patients undergoing hemodialysis. Specifically, it aims to answer the following questions: (1) What are the problems encountered by the patient during hemodialysis?, (2) How do you describe changes in your life in terms of physical and physiological, psychological and emotional, and social aspect after hemodialysis? (3) How do you cope up with the changes in life after hemodialysis? (4) How do you perceived level of life satisfaction after undergoing hemodialysis? A qualitative phenomenological approach was employed in this study to elucidate the changes among patients who are undergoing hemodialysis. The study was conducted in Hospital A located at the south. Respondents in this study were female and male middle aged undergoing hemodialysis for the past three months. The researcher wrote and secured a permission letter addressed to the Dean of the College of Health Related Sciences and to the hospital administrator. A scheduled initial interview was made with the nursing supervisor of the dialysis center and an informed consent was signed by the respondents. The researcher conducted a one-on-one interview with the respondents to answer the question of "what is the quality of life of patients undergoing hemodialysis?". Another consent was asked to record the conversation between the respondent and interviewer. After the interview was done, the researcher transcribed keywords and statements. Data analysis used was abstraction or thematic presentation by summarizing each interview. The following results where drawn from the study: Four middle-aged hemodialysis patient were presented in this study in understanding changes, problems, coping strategies and perceived level of satisfaction during hemodialysis treatment. Having respectfully given the researchers the time and space to interview different hemodialysis patient on the changes they are experiencing during treatment. All these factors experienced by the respondents were able to be managed by accepting their condition and being optimistic. All four respondents stated that they learned to accept their condition and decided to be positive while undergoing treatment. As for the level of satisfaction, all four respondents rated and perceived satisfaction in a moderate level. Since the respondents in this study were patient who undergone hemodialysis for the past three months, they were able to adjust and comply with the therapy and were able to maintain accept and maintain positive outlook in life during the early stage of treatment. Although hemodialysis patients are subjected to multiple physiological and psychological stressors and may be threatened by many potential losses and lifestyle changes, maintaining a positive environment and accepting the condition greatly influenced the patients quality of life.
Undergraduate Thesis